Ответы и объяснения

2014-01-15T00:56:08+00:00
1)
2x-0,7 > 0,3^1
2x > 0,3 + 0,7
x > 0,5
2) (x-1)/2 > 4^0 = 1
x - 1 > 2
x > 3
3) x*x +5x+8 = 2^2
x*x+5x+4 = 0
(x+1)(x+4) = 0
x1 = -1
x2 = -4
4) log(3)(lg(x+5)) =6^0 = 1
lg(x+5) = 3^1
x+5 = 10^3 = 1000
x = 995


1) 5x - 6 > 2x +3
3x > 9
x > 3
2) x - 5 < 3 ^1
x < 8
3) x^2 - 5x +10 = 4
x^2 - 5x +6 = 0
(x-2)(x-3) = 0
x1 = 2
x2 = 3
4)  log(2)log(3)(x-5) = 1/2^0 = 1
log(3)(x-5) = 2^1
x-5 = 3 ^ 2 = 9
x = 14
5)   1/2*log(3)(x) + log(3)(x) + (-1/2)*log(3)(x) = 2
(1/2 + 1 - 1/2) * log(3)(x) = 2
log(3)(x) = 2
x = 3^2 = 9